Musharaka: Alternative Financing Solution in The Pandemic of Covid 19 - Dyah Ayu Perwitasari; Mutimmah Rustianawati; Novita Lidyana (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
This research is a qualitative research which aims to examine musharaka as an alternative financing solution during the Covid 19 pandemic and focus on the calculation of profit sharing and its suitability according to Fatwa DSN No. 08 / DSN-MUI / IV / 2000. Primary data in this study are the results of interviews and secondary data are in the form of profit sharing reports of BPRS Rinjani secondary data is in the form of BPRS Rinjani profit sharing reports. The profit calculation sharing of the financing on the musharaka contract at BPRS Bumi Rinjani Probolinggo is in accordance with the Fatwa of the National Syari'ah Council of the Indonesian Ulama Council, Number: 08 / DSN-MUI / IV / 2000. The calculation of profit sharing based on profits and no amount is determined in advance. With the uncertainty of the income of bank partners (customers) during the current pandemic, the concept of musharaka financing can be used as an alternative solution in financing for both banks and partners.